Exploring nanocomposites for controlling infectious microorganisms: charting the path forward in antimicrobial strategies - Saravanan, Harish; Subramani, Tarunkarthick; Rajaramon, Shobana; David, Helma; Sajeevan, Anusree; Sujith, Swathi; Solomon, Adline Princy (Frontiers in Pharmacology, 2023)
Nanocomposites, formed by combining a matrix (commonly polymer or ceramic) with nanofillers (nano-sized inclusions like nanoparticles or nanofibers), possess distinct attributes attributed to their composition. Their unique physicochemical properties and interaction capabilities with microbial cells position them as a promising avenue for infectious disease treatment. The escalating prevalence of multi-drug resistant bacteria intensifies the need for alternative solutions. Traditional approaches involve antimicrobial agents like antibiotics, antivirals, and antifungals, targeting specific microbial aspects. This review presents a comprehensive overview of diverse nanocomposite types and highlights the potential of tailored matrix and antibacterial agent selection within nanocomposites to enhance treatment efficacy and decrease antibiotic resistance risks. Challenges such as toxicity, safety, and scalability in clinical applications are also acknowledged. Ultimately, the convergence of nanotechnology and infectious disease research offers the prospect of enhanced therapeutic strategies, envisioning a future wherein advanced materials revolutionize the landscape of medical treatment.